Determinants of bank stability in Ethiopia: A two-step system GMM estimation - Mekonnen Kumlachew Yitayaw; Yohannes Kefale Mogess; Habtamu Legese Feyisa; Wondmagegn Biru Mamo; Salah Mohammed Abdulahi (Cogent Economics & Finance, 2023)
Studies on the determinants of bank stability conclude that bank-specific and external factors affect bank financial stability. However, most of these studies are conducted in developed countries, where Banks, on average, are richer and have more liquidity. This study evaluates the effect of bank-specific and external factors on Bank Stability in a least developed country-Ethiopia using commercial banks data from 2014 to 2020. By using Two-Step System Generalized Method of Moments (GMM) estimation, we find that bank lending rate, tangibility, GDP growth rate, control of corruption, and rule of law effectiveness stabilize bank financial stability. The effect is more pronounced for Banks with high market share of mobilized capital. On the other hand, bank concentration and bank efficiency reduce bank financial stability by about 2.51 and 0.97 units, respectively. Furthermore, the effect of historical level of bank stability has a positive and significant effect on current level of bank financial stability. The implication of this result is vital for policy-makers, as it explicitly suggests that keeping bank stability today has a vital role in achieving higher bank stability in the future.
Keywords: 330; Bank Stability; Determinants; Ethiopia; System GMM; Z-score